Analyses of the Sustainable Tourism Development Factors: the Example of Sochi-City - Evgeniya V. Vidishcheva; Galina D. Bryukhanova (Centre for Behaviour and Wellness Advocacy, 2017)
The concept of sustainability is the leading trend of modern world development. This term is found in almost all government programs and strategies. Countries dependent on tourism revenues are extremely interested in sustainable development. This concept allows to minimize their environmental impact and to maximize the overall socio-economic benefits for tourist destinations. Formation and implementation of sustainability programs are long-term and expensive processes, which are influenced by factors of internal and external environment. The aim of this article is to define the role of sustainability in the tourism industry and to reveal the major factors that influence on the process. The objectives of this paper are: (i) to study theoretical base of the sustainability concept, (ii) to analyze current situation in the industry and (iii) to reveal the main factors of Sustainability tourism from Sochi-City.